Oscillation of Certain Emden-Fowler Dynamic Equations on Time Scales - Qiaoshun Yang; Lynn Erbe; Baoguo Jia (Abstract and Applied Analysis)
We deal with the oscillation of a generalized Emden-Fowler dynamic equation in the form (rtZΔtα-1ZΔt)Δ+f(t,x(δ(t)))=0. We establish some new oscillation criteria for the equation, which improve some of the main results of (H. Liu and P. Liu, 2013). Some examples are given to illustrate the new results.